“The perfect library”Carrie Chapman Catt and the authoritative historiography - Claire Delahaye (Nuevo mundo - Mundos Nuevos, 2014)
The very act of remembering was at the core of power dynamics in the suffrage movement, during the years of struggle and after the ratification of the 19th amendment in 1920. In the late 1930s, Carrie Chapman Catt, the former president of the National American Woman Suffrage Association and the International Woman Suffrage Alliance, decided to create her own “perfect library” on the woman suffrage movement, that she bequeathed to the Library of Congress in Washington. This paper explores the authoritative dimension of Catt’s endeavor and her effort to control the memory of the movement. Catt made it a personal affair: she obliterated historical accurateness to favor her vision, her agenda and her legacy. She saw herself as the sole custodian of suffragist remembrance.